Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (De Boeck Supérieur, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."–Quatrième de couverture.
Section: xxi, 326 pages : illustrations ; 24 cm.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. – From publisher's description. Contenu : Preface – Acknowledgements – About the author – The study of gender – Researching sex and gender – Gender stereotypes: masculinity and femininity – Hormones and chromosomes – Theories of gender development – Developing gender identity – Intelligence and cognitive abilities – Emotion – Relationships – Sexuality – School – Careers and work – Health and fitness – Stress, coping, and psychopathology – Treatment for mental disorders – How different? – References – Index.
Section: xix, 539 pages ; 26 cm
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

The lived experiences of black undergraduate lesbian students at a rural South African university - Nela, K.; Vawdab, N.; Mbokodoc, L.; Govender, S. (Gender and Behaviour, 2017)
Malgré l'acceptation croissante des personnes lesbiennes, gays, bisexuelles, transgenres et intersexes (LGBTI), de nombreuses études indiquent encore que de nombreuses discriminations existent toujours. Les lesbiennes d'Afrique australe sont quotidiennement victimes de violences physiques et verbales et de viols correctifs. Le but de cette étude était d'explorer les expériences vécues par des étudiantes lesbiennes noires de premier cycle dans une université rurale en Afrique du Sud. Une approche de recherche qualitative utilisant un plan de recherche phénoménologique a été utilisée. L'échantillon était composé de quinze étudiantes lesbiennes noires de premier cycle âgées de 18 à 25 ans. Les données ont été collectées dans deux groupes de discussion et analysées à l'aide d'une analyse phénoménologique interprétative (IPA). L'homophobie, le harcèlement, y compris les agressions physiques, et la non-acceptation étaient des expériences quotidiennes chez les participantes lesbiennes. Cela incluait la discrimination de la part des pairs, du personnel universitaire et des organisations religieuses. Des expériences positives, comme la rencontre de nouveaux amis partageant la même orientation sexuelle et la découverte de l'université comme espace libre pour explorer leur sexualité, ont été trouvées.
Number: 3
Keywords: afrique; afrique du sud; approches et analyses; discipline; droits des femmes*; hétérosexisme; lesbophobie; personnes lesbiennes; psychologie; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; étudiantes de premier cycle

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La haine et l'amour, la boîte noire du féminisme? Une critique de l'éthique du dévouement - Molinier, Pascale (Nouvelles Questions Feministes, 2004)
Les soins étant réalisés majoritairement par des femmes, on tend à considérer l’amour (des malades, des enfants) « naturel » et normal. Or, le travail de soin peut également générer de la haine envers les personnes dépendantes. Celle-ci n’est pas moins normale que l’amour et sa prise en compte modifie l’analyse des situations de soins. Pour l’heure, la haine est occultée dans les traditions savantes, en particulier dans les théories de l’éthique du dévouement, comme dans les témoignages des travailleuses, ainsi que le suggère une enquête réalisée auprès d’auxiliaires de puériculture. Il en résulte un déficit de visibilité du travail qui permet de conjurer la haine et la violence
Keywords: approches et analyses; care; discipline; discours dominant; projet charge mentale; psychologie; ressource en ligne; sciences humaines; sexisme; soins aux enfants; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences